2021
DOI: 10.1177/0091217421994078
|View full text |Cite
|
Sign up to set email alerts
|

Catatonia in the medically ill: Differences and parallels in etiology, phenomenology and management

Abstract: Objective Catatonia is a disorder characterized by psychomotor symptoms. The etiology, symptomatology, response and outcome of catatonia in the medically ill has not been vigorously studied. Those who have catatonia associated with another mental disorder versus. catatonic disorder due to another medical condition may differ. The aim of this study is to study the causes, phenomenology and outcomes of medically ill patients with catatonia and explore differences among those who have catatonia associated with ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In the 11th revision of the International Classification of Diseases (ICD-11), new diagnostic grouping has been added and catatonia can be divided into three conditions: (1) associated with another mental disorder; (2) induced by psychoactive substances, including medications; and (3) secondary catatonia due to a medical condition [2]. These changes made catatonia no longer limited to schizophrenia, but become an independent nosological entity, facilitating the identification of catatonia in the context of other psychotic disorders, the use of substances and general medical conditions, such as encephalitis [3,4]. Several studies revealed that serious medical complications might occur if catatonia cannot be recognized and interventions are not initiated in a timely manner [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the 11th revision of the International Classification of Diseases (ICD-11), new diagnostic grouping has been added and catatonia can be divided into three conditions: (1) associated with another mental disorder; (2) induced by psychoactive substances, including medications; and (3) secondary catatonia due to a medical condition [2]. These changes made catatonia no longer limited to schizophrenia, but become an independent nosological entity, facilitating the identification of catatonia in the context of other psychotic disorders, the use of substances and general medical conditions, such as encephalitis [3,4]. Several studies revealed that serious medical complications might occur if catatonia cannot be recognized and interventions are not initiated in a timely manner [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This change was further expanded in the DSM-V, where catatonia is postulated to independently arise in the context of multiple different psychiatric and other medical etiologies. Regardless of etiology, studies and case reports have shown that catatonia responds similarly to ECT ( Espi Forcen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The first is the extent to which particular catatonic signs associate with the diagnoses underlying the catatonia. One retrospective study of 40 patients with catatonia in a general hospital found that stereotypy, mannerism, waxy flexibility and impulsivity were each more common where catatonia was due to a psychiatric disorder (such as depression or schizophrenia), compared to cases where catatonia was due to an underlying medical condition (such as autoimmune encephalitis or a space-occupying lesion) ( 13 ). Another study of 140 patients with catatonia in a specialist hospital found that patients with psychotic disorders had more posturing than those with a medical disorder, but there were no differences between those with psychotic and those with affective disorders ( 14 ).…”
Section: Introductionmentioning
confidence: 99%